Expert knowledge elicitation with SHELF: uncertainty and probability - O'Hagan, Anthony (Henry Stewart Talks, 2023)
Uncertainty and probability, The nature of elicitation and probability, Uncertainty and hard decisions, The importance of expert knowledge, Science and subjectivity, Applications of elicitation, The power curve